Regulating Chlorine and Hydrogen Atom Transfer for Selective Photoelectrochemical C─C Coupling by Cu‐coordination Effect at Semiconductor/Electrolyte Interfaces - Qiaozhen Li; Kun Dang; Lei Wu; Siqin Liu; Yuchao Zhang; Jincai Zhao (Advanced Science)
Abstract Semiconductor‐based photoelectrochemical (PEC) organic transformations usually show radical characteristics, in which the reaction selectivity is often difficult to precisely control due to the nonselectivity of radicals. Accordingly, several simple organic reactions (e.g., oxidations of alcohols, aldehydes, and other small molecules) have been widely studied, while more complicated processes like C─C coupling remain challenging. Herein, a synergistic heterogeneous/homogeneous PEC strategy is developed to achieve a controllable radical‐induced C─C coupling reaction mediated by the copper‐coordination effect at the semiconductor/electrolyte interfaces, which additionally exerts a significant impact on the product regioselectivity. Through experimental studies and theoretical simulations, this study reveals that the copper‐chloride complex effectively regulates the formation of chloride radicals, a typical hydrogen atom transfer agent, on semiconductor surfaces and stabilizes the heterogeneous interfaces by suppressing the radical‐induced surface passivation. Taking the Minisci reaction (the coupling between 2‐phenylquinoline and cyclohexane) as a model, the yield of the target C─C coupling product reaches up to 90% on TiO2 photoanodes with a selectivity of 95% and long‐term stability over 100 h. Moreover, such a strategy exhibits a broad scope and can be used for the functionalization of various heteroaromatic hydrocarbons.